STUDI KARAKTERISTIK LALU LINTAS DARI PENERAPAN LAJUR CONTRAFLOW DI JALAN TOL CAWANG – SEMANGGI (STUDI KASUS: ZONA MASUK) - Fauzan, Ivan; Sumabrata, Jachrizal; Marino, Alan (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Jakarta, as a sprawling metropolitan, is burdened with the daily activities of its population and their everyday movements. The huge amount of vehicles, especially light vehicles, moving towards the business districts such as Semanggi has filled to capacity the toll roads, more specifically the Jakarta Inner Ring Road, and thus traffic is the result. To increase the capacity and to decrease traffic, PT Jasa Marga has implemented a contraflow lane that starts from km 01+600 until km 08+600. This research is to study the traffic characteristics from the contraflow lane, with the focus at the entrance zone and the middle zone. The emphasis of this study is to understand the performance and effectivity of contraflow lane and the effect it has on the toll road in regards of the traffic characteristics (capacity, volume, speed and density). The method of this research is to compare existing conditions that is surveyed first-hand with standards set from the Public Works Minister, MKJI (Manual Kapasitas Jalan Indonesia) and Greenshield’s Theory. The result of this research shows that the implementation of a contraflow lane decreases the degree of saturation from those greater than 0.75 to less than 0.75, by significantly increasing road capacity. Thus it can be concluded that the contraflow lane is effective and is an excellent means to decrease traffic.